2012
DOI: 10.5539/jas.v5n1p95
|View full text |Cite
|
Sign up to set email alerts
|

Deodorizing Effects of Phlorotannins from Edible Brown Alga Eisenia bicyclis on Methyl Mercaptan

Abstract: In search for new deodorizing compounds, we were identified three phlorotannins; eckol (1), dioxinodehydroeckol (2) and dieckol (3) from edible brown seaweed Eisenia bicyclis and characterized by Fast-atom bombardment mass spectrometry (FAB-MS) and nuclear magnetic resonance (NMR). The deodorizing activity of those compounds was evaluated against methyl mercaptan, which is well known as a major causative material of halitosis and off-flavor. Among them, compound 3 exhibited the highest deodorizing activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Thus, the use of either RP-SPE or RP-HPLC combined with NP-CC provides two dimensions of separation that, in many cases, replace the need for column approaches. Nonetheless, some studies have reported the use of RP-CC of phlorotannins [32,76,151,159,172,177,178,182] or coumarins and phenolic acids [21], mostly with octadecyl-derivatized stationary phases. This matrix is the most widespread RP phase since it provides excellent resolution for a wide variety of organic compounds while using aqueous and low toxicity polar solvents for elution (instead of the hydrophobic ones associated with NP-CC, which are costly, toxic, and polluting).…”
Section: Column Chromatographymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the use of either RP-SPE or RP-HPLC combined with NP-CC provides two dimensions of separation that, in many cases, replace the need for column approaches. Nonetheless, some studies have reported the use of RP-CC of phlorotannins [32,76,151,159,172,177,178,182] or coumarins and phenolic acids [21], mostly with octadecyl-derivatized stationary phases. This matrix is the most widespread RP phase since it provides excellent resolution for a wide variety of organic compounds while using aqueous and low toxicity polar solvents for elution (instead of the hydrophobic ones associated with NP-CC, which are costly, toxic, and polluting).…”
Section: Column Chromatographymentioning
confidence: 99%
“…At last, size exclusion chromatography (SEC-CC) using Sephadex LH-20 has been repeatedly used in the fractionation of macroalgae polar extracts [60,76,77,88,115,151,156,157,174,175,[177][178][179][180][181][182]. The separation of compounds in Sephadex LH-20 is promoted by the metabolites' molecular size, but also by its solubility in the eluent.…”
Section: Column Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…Various fruits and vegetables have been shown to lower the levels of volatiles (Mirondo & Barringer, 2016). Particularly, the deodorizing activity of natural polyphenols has been extensively evaluated (Kida et al., 2002; Kim et al., 2013; Lodhia et al., 2008; Makhotkina & Kilmartin, 2010; Munch & Barringer, 2014; Negishi et al., 2002; Negishi et al., 2004; Yasuda, & Arakawa, 1995). Green tea extract (GTE), black tea extract (BTE), and grape seed extract (GSE) contain high concentrations of flavonoids, such as catechins, and other polyphenol compounds with numerous reported beneficial effects on health (Gibis et al., 2016; Otton et al., 2018; Pan et al., 2016).…”
Section: Introductionmentioning
confidence: 99%